The History of Economic Thought in the International Encyclopedia of the Social Sciences - Letiche, John M. (Journal of Economic Literature, 1969)
ion, he very much doubted that abstraction could provide either understanding of the real world or, by itself, safe guidance for the legislator or statesman. Although Smith failed to absorb some of the valuable analytical contributions of Hume, the physiocrats, and Turgot, he repeatedly amended his major works by bringing into his discussion some neglected variable, some fresh observation of fact, some new objective. He resorted profusely to qualifications, and his models were therefore not rigorous. is arguable, however, by those who, if forced to choose, prefer realism, or at least the pursuit of it, to rigor and elegance of analysis, that both of his major works are on the whole made better by the qualifications he sprinkled in their pages and that he would have made them still better, although still untidier, if he had used even more qualifying adjectives or phrases [28, p. 327]. It is difficult to exaggerate the intellectual stimulus to be derived from reading this and the numerous other provocative bibliographical articles published in the En-